PENGARUH EARNING PER SHARE, STRUKTURAL MODAL DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI - Michael Sinaga; Zufrizal Harahap; Sri Rahayu (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
The stock price is the main factor that is considered by investors in making investment. The purpose of this study is to observe the relationship between earnings per share, capital structure and financial performance with stock prices. The type of research data that can be used is a quantitative approach. The sampling that can be used is the purposive sampling technique, and there are 19 companies in the mining sector that are sampled in 44 companies. The data source used is secondary data obtained from the Indonesia Stock Exchange, 2017 to 2019. The results of this study indicate that, individually, earnings per share have a positive and significant impact on stock prices and structural capital has a negative and significant impact on stock prices, while financial performance has no significant effect on stock prices.